MUSCLE MASS AND MUSCLE FUNCTION IN PATIENTS WITH CHRONIC KIDNEY DISEASE: COMPARATIVE ASSOCIATIONS OF SARCOPENIA INDEX, CREATININE/CYSTATIN C RATIO, AND ESTIMATED GLOMERULAR FILTRATION RATES DIFFERENCE (Vietnam Journal of Community Medicine, 2026)
Objective: To compare the associations of SI, the Cre/CysC ratio, and eGFRdiff with muscle mass and muscle function in patients with chronic kidney disease.Methods: This cross-sectional study included 90 patients with chronic kidney disease. Muscle mass was assessed using the SMI. Muscle function was evaluated by HGS and walking time as a measure of physical performance. Associations of SI, Cre/CysC, and eGFRdiff with SMI, HGS, walking time, BMI, and age were analyzed using Pearson or Spearman correlation coefficients as appropriate for data distribution.Results: SI showed moderate to strong associations with muscle mass and function, including positive correlations with SMI (r = 0.488; p < 0.001) and HGS (r = 0.654; p < 0.001), and negative correlations with walking time (r = -0.429; p < 0.001) and age (r = -0.506; p < 0.001), while showing no association with BMI (r = 0.08; p = 0.428). The Cre/CysC ratio was also significantly associated with SMI (r = 0.377; p < 0.001), HGS (r = 0.537; p < 0.001), walking time (r = -0.317; p = 0.002), and age (r = -0.215; p = 0.042), and was not associated with BMI (r = -0.084; p = 0.432). In contrast, eGFRdiff was not associated with SMI, walking time, or BMI, and showed only a weak association with HGS (r = 0.231; p = 0.028).Conclusion: In patients with chronic kidney disease, SI demonstrates the strongest and most consistent associations with measures of muscle function and aging, whereas the Cre/CysC ratio reflects both muscle mass and muscle function with minimal influence from BMI. In contrast, eGFRdiff shows limited associations with muscle-related parameters. These findings suggest that SI and the Cre/CysC ratio are more suitable than eGFRdiff for reflecting muscle status in patients with chronic kidney disease.
Keywords: Chronic kidney disease, muscle mass, muscle function, sarcopenia index, creatinine/cystatin C ratio, eGFRdiff.